2020
DOI: 10.1074/jbc.ra119.012256
|View full text |Cite
|
Sign up to set email alerts
|

Impaired folate binding of serine hydroxymethyltransferase 8 from soybean underlies resistance to the soybean cyst nematode

Abstract: Management of the agricultural pathogen soybean cyst nematode (SCN) relies on the use of SCN-resistant soybean cultivars, a strategy that has been failing in recent years. An underutilized source of resistance in the soybean genotype Peking is linked to two polymorphisms in serine hydroxy-methyltransferase 8 (SHMT8). SHMT is a pyridoxal 5′-phosphate–dependent enzyme that converts l-serine and (6S)-tetrahydrofolate to glycine and 5,10-methylenetetrahydrofolate. Here, we determined five crystal structures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 46 publications
(52 reference statements)
2
41
0
Order By: Relevance
“…Any disruption of this area may lead to loss of tetramerization (Jagath et al, 1997a). Therefore, our data support the idea that, at least in soybean, the cytosolic GmSHMT08 is present as a tetramer, as has been suggested earlier [ 9 , 10 , 29 , 52 ]. Moreover, mutations affecting the GmSHMT08 subunits, including dimerization and tetramerization residues, negatively impacted the GmSNAP18/GmSHMT08/GmPR08-Bet VI multi-protein complex interaction, suggesting that the presence of the GmSHMT08 tetramer is essential for the multi-protein complex.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Any disruption of this area may lead to loss of tetramerization (Jagath et al, 1997a). Therefore, our data support the idea that, at least in soybean, the cytosolic GmSHMT08 is present as a tetramer, as has been suggested earlier [ 9 , 10 , 29 , 52 ]. Moreover, mutations affecting the GmSHMT08 subunits, including dimerization and tetramerization residues, negatively impacted the GmSNAP18/GmSHMT08/GmPR08-Bet VI multi-protein complex interaction, suggesting that the presence of the GmSHMT08 tetramer is essential for the multi-protein complex.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we isolated a novel GmSHMT08 G357R carrying a missense mutation one residue away from the N358Y SNP found between Forrest and Essex, increasing the total of isolated Gmshmt08 EMS missense mutants to 17 ( Figure S4 ). It has recently been reported that the Forrest-specific polymorphic substitution N358Y impacted the mobility of a loop near the entrance of the (6S)-tetrahydrofolate-binding site, severely reducing its affinity for folate and dramatically impairing enzyme activity in Forrest GmSHMT08 [ 52 ]. Interestingly, an EMS mutation at the Gly357 residue resulted in the highest increase in female index (FI > 113%) ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations